ON (?m, I) - LACUNARY STATISTICAL CONVERGENCE OF ORDER ? - Et, Mikail; Sengul, Hacer (Univ Prishtines, 2016)
In this study, using the generalized difference operator Delta(m), we introduce the concepts of (Delta(m) , I) -lacunary statistical convergence of order alpha and lacunary strong Delta(m)(p)-summability of order alpha of sequences and give some relations about these concepts.
Keywords: Spaces